OPTIMASI NIRKABEL LOCAL AREA NETWORK FAKULTAS TEKNIK KAMPUS SUDIRMAN UNIVERSITAS UDAYANA - Yuda Krisnawan, Komang; Putra Sastra, Nyoman; Wirastuti, N.M.A.E.D. (Jurnal SPEKTRUM, 2018)
One of the changes in the field of telecommunications is the use of wireless technology. Wireless technology is applied to computer networks better known as Wireless Local Area Network (WLAN). Network coverage quality measurements can be seen from categories of delay or suspension, excess queues on the network, increased traffic, and output results. By using Wi-Fi Analyzer and Ekahau software we get the Quality of Service (QoS) value to see how good the coverage of the existing wireless network is. The result of the measurement is analyzed to get the adjustment of the wireless area coverage formula so that it can find the maximum range used as a reference in placing the ideal access point. The addition of access point points is done on all buildings where at some point the area can not be reached as a whole.